2016
DOI: 10.1016/j.neulet.2016.07.053
|View full text |Cite
|
Sign up to set email alerts
|

GABA predicts visual intelligence

Abstract: HighlightsCortical GABA levels correlate with visuo-spatial IQ and surround suppression.Higher levels predict higher intelligence and stronger surround suppression.Results provide mechanism linking surround suppression and intelligence.Results suggest role of cortical GABA levels in determining cognitive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 29 publications
(45 reference statements)
0
55
4
Order By: Relevance
“…This agrees with an earlier observation that blocking GABA in macaque MT had no effect on spatial suppression 36 (see also 37 ). However, our MRS findings appear to conflict with reports that greater mid-occipital GABA was associated with stronger surround suppression during contrast perception 25,27 . This discrepancy may be related to the methods for quantifying suppression, and / or differences in the role of inhibition during perception of contrast and motion.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This agrees with an earlier observation that blocking GABA in macaque MT had no effect on spatial suppression 36 (see also 37 ). However, our MRS findings appear to conflict with reports that greater mid-occipital GABA was associated with stronger surround suppression during contrast perception 25,27 . This discrepancy may be related to the methods for quantifying suppression, and / or differences in the role of inhibition during perception of contrast and motion.…”
Section: Discussioncontrasting
confidence: 99%
“…Although this paradigm has been posited as a behavioral index for inhibition, we did not find a major role for GABA in determining the strength of spatial suppression. While a few studies have probed the neurochemical underpinnings of perceptual suppression in humans 17,[25][26][27] , much of our current insight into the neural mechanisms of suppression and inhibition has come from work in animal models. Some reports suggest that GABAergic inhibition plays a direct role in surround suppression within visual cortex [28][29][30][31] , while others have indicated that this suppression occurs via withdrawal of excitation [32][33][34][35] , that may be balanced by reduced inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to dopamine, GABA is a neurotransmitter that is known to be related to eye blinks and correlated with level of intelligence (Colzato et al, 2008 ). Cook et al ( 2016 ) demonstrated a strong positive correlation between visual intelligence and cortical GABA concentrations ( r = 0.83, p = 0.005). Subjects with high levels of GABA in the primary visual cortex performed better on a matrix reasoning IQ sub-test.…”
Section: Discussionmentioning
confidence: 95%
“…Magnetic resonance spectroscopy (MRS) has been shown to robustly estimate in-vivo GABA levels. Recent studies in younger adults 24 26 , and several patient groups 27 , 28 , have shown that such estimates of GABA concentration correlate with the strength of several perceptual effects that are considered to rely on inhibitory function, namely: surround contrast suppression 24 , 28 , orientation discrimination 29 , and binocular rivalry 26 , 27 . Consequently, GABA measurement by MRS has the potential to be a useful tool to explore whether changes to presumed perceptual inhibitory strength within the visual system can be explained, at least partially, by differences in GABA levels between individuals.…”
Section: Introductionmentioning
confidence: 99%